Intelligent Plant Watering System with Arduino Uno - Azeez Ali; B. Sai Kumar; K. Durga Prasad; K. Chiranjeevi (International Journal of Manufacturing and Production Engineering, 2023)
The working version of this intelligent irrigation system reduces water use by dynamically watering plants based on their requirements. The system calculates water needs by recording soil temperature and moisture using Arduino electronics and soil moisture sensors. Water is released quickly and is saved up to 80% by triggering a solenoid valve. The affordable approach works well for farming, maintaining lawns, and maintaining parks, lowering hazards and streamlining work while conserving water in an era of water constraint. For plant lovers who want to make sure their plants are watered constantly, building a watering system using an Arduino Uno board can be a terrific project. A well- liked microcontroller board known as the Arduino Uno can be configured to operate a number of electronic gadgets.
Keywords: Intelligent Plant Watering System with Arduino Uno